Design and analysis of triangular shaped patch with slot antenna for UHF RFID reader - Mohd Hisyam, Ariff; Muhammad Zulkhairi, Saidin; Mohammad Fadhil, Abas; Noor Zirwatul Ahlam, Naharuddin; Nor Hadzfizah, Mohd Radi; Rahimah, Jusoh (AIP Publishing, 2025)
This paper aims to introduce a novel design and analysis of a triangular patch antenna tailored for Ultra High Frequency (UHF) Radio Frequency Identification (RFID) reader applications, capitalizing on the advantages offered by UHF RFID systems. The antenna design leverages FR-4 material, chosen for its medium cost and lightweight properties. The proposed antenna configuration comprises a triangular antenna patch on top of a rectangular substrate. Tuned to operate within the frequency range of 919 MHz to 923 MHz, allocated for Malaysia's UHF RFID system, the antenna promises optimal performance. Utilizing CST Microwave Studio, a Voltage Standing Wave Ratio (VSWR) of 1.02 and a gain of 6.08 dB at 921 MHz were achieved. The study also explores key antenna parameters including radiation pattern, return loss, and bandwidth. Subsequently, the antenna's functionality will be validated with an industrial UHF reader module, demonstrating its capability to read UHF tag data adhering to ISO 16000-C standards, particularly those manufactured by Avery Dennison. All parameter analyses were conducted using CST Microwave Studio 2021.